The role of UK local government in delivering on net zero carbon commitments: You've declared a Climate Emergency, so what's the plan?. (July 2021) - Gudde, Peter; Oakes, Justine; Cochrane, Peter; Caldwell, Nicholas; Bury, Nic
Abstract: Local authorities in the United Kingdom are recognised by central government as key agents to achieving the national net zero target aimed at stabilising global temperatures at or below 1.5 degrees in line with the Paris Climate Agreement. Since 2018, over 75% of local authorities have declared climate emergencies committing to achieving net zero greenhouse gas emissions. This paper presents the findings of a review of official public records published by 308 local authorities, City Regions and Combined Authorities declaring climate emergencies. Significant variability and ambiguity were found in their scope of commitment, delivery planning arrangements and funding plans. Few local authorities have embraced the concept of Citizens' Climate Assemblies as a way of engaging civil society. A follow-up review showed that although there is near uniformity of political desire to tackle climate change, action planning is very much work in progress with tight delivery timelines for the majority, significant divergence in approaches, and an unclear role for the citizen. The research concludes that without a local-authority specific Net Zero duty and well-designed and financed delivery models, local authorities will choose their own routes and finishing lines shaped by a complex ecosystem of internal and external factors. A governance framework is proposed based on the concept of local area climate contracts to bring together national and local Net Zero ambitions. Highlights: Since 2018 over 75% of UK local authorities have declared climate emergencies. 75% have selected a Net Zero target date of 2030. Only 2% had a published delivery plan at the time of their net zero declaration. There is no pattern to public engagement with few establishing Climate Assemblies. A governance framework is proposed to harness local and national Net Zero ambitions.